A Multidimensional Modeling Approach to Classify the Poverty Levels of Households - Udayanga Rukshan; Hasitha Erandi; Osadee Peiris; Sanjeewa Perera (Directorate for Research and Innovation (DRI) ITB, 2026)
The conventional method for poverty measurement is the poverty line, which is based only on household income and expenditure. The poverty line can be used to determine whether a given household is poor or not. However, to capture the true nature of poverty, many factors other than income and expenditure should be considered. In this study, we developed a model for developing countries under a multidimensional framework to classify poverty levels of poor households by incorporating a fuzzy approach. The poverty levels are categorized into three levels and threshold values are determined for each level. In order to generate results, we used relevant statistical data from Sri Lanka. The results of this study indicated that individual education, income, and housing characteristics are the most significant factors in determining the poverty level of individual households in Sri Lanka. Further, the developed model provides a menu of focused factors and a policy tool for policymakers to allocate and distribute subsidies for needy areas.